Communicating future sea-level rise uncertainty and ambiguity to assessment users - Kopp, Robert E; Oppenheimer, Michael; O’Reilly, Jessica L; Drijfhout, Sybren S; Edwards, Tamsin L; Fox-Kemper, Baylor; Garner, Gregory G; Golledge, Nicholas R; Hermans, Tim H. J; Hewitt, Helene T; Horton, Benjamin P; Krinner, Gerhard; et al. (Nature climate change, 2023)
Future sea-level change is characterized by both quantifiable and unquantifiable uncertainties. Effective communication of both types of uncertainty is a key challenge in translating sea-level science to inform long-term coastal planning. Scientific assessments play a key role in the translation process and have taken diverse approaches to communicating sea-level projection uncertainty. Here we review how past IPCC and regional assessments have presented sea-level projection uncertainty, how IPCC presentations have been interpreted by regional assessments and how regional assessments and policy guidance simplify projections for practical use. This information influenced the IPCC Sixth Assessment Report presentation of quantifiable and unquantifiable uncertainty, with the goal of preserving both elements as projections are adapted for regional application.The extent to which sea level will rise under climate change is uncertain, with some of this uncertainty being quantifiable and some unquantifiable. This Review discusses past and present presentations of this uncertainty in IPCC and regional assessments, as well as their influence on users' interpretations.